2010
DOI: 10.1542/peds.2009-0172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Jaundice and Phototherapy on the Frequency of First-Year Outpatient Visits

Abstract: Objective The objective of this study was to determine whether either hyperbilirubinemia or inpatient phototherapy is associated with increased subsequent outpatient visit rates, a possible effect of the “vulnerable child syndrome.” Methods We compared 3 groups of otherwise well term and late-preterm infants who were born between 1995 and 2004 in Northern California Kaiser hospitals: group 1 never had a documented total serum bilirubin (TSB) level ≥12 mg/dL (n = 128 417); group 2 had a TSB level ≥17 and <23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
(15 reference statements)
1
4
1
Order By: Relevance
“…Approximately half (51%) of all readmissions occurring 2 weeks after birth were attributable to NHB [27]. The increase in physician office visits we reported was also consistent with available literature, which found that NHB was associated with increased parental awareness, and newborns receiving phototherapy had higher rates of outpatient visits [28].…”
Section: Discussionsupporting
confidence: 85%
“…Approximately half (51%) of all readmissions occurring 2 weeks after birth were attributable to NHB [27]. The increase in physician office visits we reported was also consistent with available literature, which found that NHB was associated with increased parental awareness, and newborns receiving phototherapy had higher rates of outpatient visits [28].…”
Section: Discussionsupporting
confidence: 85%
“…This can interfere with breastfeeding and bonding and cause parental anxiety. [15][16][17][18] Calibration shifts in laboratory assays can have major clinical implications. While theoretical models can predict these effects, it is rare to capture the consequential extent of the…”
Section: Discussionmentioning
confidence: 99%
“…31 In another study, parents of children with feeding and crying problems in infancy necessitating a change in formula were more likely to perceive their child as vulnerable .3 years later, despite being no more likely to report allergies, asthma, or eczema for their child. 32 Finally, parents of infants with jaundice or phototherapy exposure are more likely to seek medical attention for their child well after jaundice resolution, 33 perceive subsequent illnesses as moderate or severe, and fear leaving their baby with any other caregiver. 34 Diagnoses also affect how children are treated by society.…”
Section: Psychological Effectsmentioning
confidence: 99%